A cost-effectiveness analysis of traditional and geographic information system-supported microplanning approaches for routine immunization program management in northern Nigeria. Issue 6 (5th February 2020) - Ali, Disha; Levin, Ann; Abdulkarim, Masduq; Tijjani, Usman; Ahmed, Bakoji; Namalam, Faruk; Oyewole, Femi; Dougherty, Leanne
Abstract: Effective RI microplanning requires accurate population estimates and maps showing health facilities and locations of villages and target populations. Traditional microplanning relies on census figures to project target populations and on community estimates of distances, while GIS microplanning uses satellite imagery to estimate target populations and spatial analyses to estimate distances. This paper estimates the cost-effectiveness of geographical information systems (GIS)-based microplanning for routine immunization (RI) programming in two states in northern Nigeria. For our cost-effectiveness analysis, we captured the cost of all inputs for both approaches to capture the incremental cost of GIS over traditional microplanning and present the incremental cost-effectiveness ratios for each vaccine-preventable illness, death, and disability-adjusted life year (DALY) averted. We considered two scenarios for estimating vaccine requirements for each microplanning approach, one based on administrative vaccination coverage rates and one based on National Nutrition and Health Survey rates. With the administrative rates, GIS microplanning projected approximately 194, 000 and 157, 000 more required vaccinations than traditional microplanning in Bauchi and Sokoto States; with the survey rates, the additional number of vaccinations required was nearly 113, 000 in Bauchi and about 47, 000 in Sokoto. For each state under each scenario, we present numbers of and costs per measles and pertussis cases, deaths, and DALYs averted by the additional vaccinations, as well as annual costs. As expected, GIS-based microplanning incurs higher costs than traditional microplanning, due mainly to the additional vaccinations required for populations previously unreached. Our estimates of cost per DALY averted suggest, however, that GIS microplanning is more cost-effective than traditional microplanning in both states under both coverage scenarios and that the higher costs incurred by GIS microplanning are worth adopting.